Substantiating rational parameters of a method for shrinkage ore stoping while developing thin- vein steeply inclined deposits - Shyrin, Leonid; Koroviaka, Yevhenii; Rastsvietaiev, Valerii; Denyshchenko, Oleksandr (My University, 2018)
Objective of the paper is to substantiate rational ore-stoping technique while using small wells in the context of thin-vein steeply inclined deposit mining. The technique is based upon the repeated field studies and simulation of ore drawing processes for shrinkage ore stoping in terms of the oriented drilling of periphery holes. A design of a blast-hole charge with low-density porous intermediate layer has been proposed as a result as well as a mechanism of shock-wave propagation within rock mass in the process of thin steeply inclined vein stoping. Scientific novelty is represented by means of analytical results of scientific sources, and dependences of ore losses on the vein wall hypsometry resulting from shrinkage stoping in the context of the technique being proposed. Practical relevance is to substantiate rational parameters of the ore-stoping technique being proposed. The technique involves designs of blast-hole charges with low-density porous intermediate layer in stemming. Moreover, the technique proposes to place the intermediate low-density stemming layer right after a blast hole was charged with explosives and live primers were inserted.